Calistung assistance and training students through the Program Kampus Mengajar - Fitriyani Fitriyani; Angga Hadiapurwa (Universitas Pendidikan Indonesia, 2023)
In Indonesia, there is an Independent Campus Learning Curriculum (MBKM) which aims to produce graduates who are competent in various fields of knowledge and skills. The Teaching Campus Program is in the context of education in remote areas that lack supporting facilities and significant educational disparities. Reading, writing, and arithmetic (Calistung) skills are essential to education. However, at the UPTD SD NEGERI 2 Cantigi Kulon, this is a problem because students' Calistung skills could be higher based on observations and interviews with the school. To overcome this problem, the student team in the Teaching Campus program carried out mentoring and training activities as a concrete step in overcoming students' difficulties in reading, writing, and arithmetic abilities, as well as helping students and teachers in the learning process to improve Calistung abilities as the basis of literacy and numeracy. This service uses mentoring and training methods. As a result of this activity, students experienced increased reading, writing, and arithmetic skills. With a directed approach and the proper support, students can overcome obstacles in Calistung and achieve better academic achievement. Abstrak Di Indonesia, terdapat Kurikulum Merdeka Belajar Kampus Merdeka (MBKM) yang bertujuan untuk menghasilkan lulusan yang kompeten dalam berbagai bidang keilmuan dan keterampilan. Program Kampus Mengajar merupakan program dalam konteks pendidikan di daerah terpencil yang kekurangan sarana pendukung dan kesenjangan pendidikan yang signifikan. Keterampilan membaca, menulis, dan berhitung (Calistung) adalah dasar yang penting dalam pendidikan namun di UPTD SD NEGERI 2 Cantigi Kulon hal ini justru menjadi permasalahan karena kemampuan Calistung siswa yang rendah berdasarkan hasil observasi dan wawancara dengan pihak sekolah. Untuk mengatasi masalah tersebut, maka tim magasiswa pada program Kampus Mengajar melakukan kegiatan pendampingan dan pelatihan sebagai langkah konkret dalam mengatasi masalah peserta didik dalam kemampuan membaca, menulis, dan berhitung, serta membantu peserta didik dan guru dalam proses pembelajaran untuk meningkatkan kemampuan calistung sebagai dasar dari literasi dan numerasi. Pengabdian ini menggunakan metode pendampingan dan pelatihan. Hasil dari kegiatan ini, peserta didik mengalami peningkatan kemampuan membaca, menulis, dan berhitung. Dengan adanya pendekatan yang terarah dan dukungan yang tepat, peserta didik dapat mengatasi hambatan dalam calistung dan mencapai prestasi akademik yang lebih baik. Kata Kunci: Calistung; Kampus Mengajar; Pendampingan Calistung